Solvent-free mechanochemical conversion of 3-ethoxysalicylaldehyde and primary aromatic amines to corresponding Schiff-bases. Issue 1 (7th January 2015) - Tigineh, Getinet Tamiru; Wen, Yuh-Sheng; Liu, Ling-Kang
Abstract Mechanochemical processes are both solvent-free and less energy consuming than standard solution reactions and are rapidly becoming popular as green and sustainable alternative to conventional solution-based processes. In this paper, fifteen Schiff-bases of differently functionalized solid primary aromatic amines were successfully synthesized using 1:1 molar ratio of 3-ethoxysalicylaldehyde to solid amine, by co-grinding in mortar with a pestle for 2–10 min under solvent-free environment at room temperature. Nine of fifteen were synthesized for the first time and the Schiff-bases were investigated by analytical and spectroscopic techniques. The excellent conversion to products, with virtually zero work-up, and isolation of species, which cannot be obtained in solution, make the mechanochemical approach a worthwhile click and green method for Schiff-base synthesis.